Control of clonorchiasis in Korea: effectiveness of health education for community leaders and individuals in an endemic area. Issue 9 (26th May 2014) - Oh, Jin‐Kyoung; Lim, Min Kyung; Yun, E. Hwa; Cho, Heeyoun; Park, Eun Young; Choi, Min‐Ho; Shin, Hai‐Rim; Hong, Sung‐Tae
Abstract Objectives To develop effective intervention programmes to control Clonorchis sinensis infection, three interventions were evaluated in a clonorchiasis‐endemic area of Korea. Methods Four thousand two hundred and sixty‐seven voluntary participants in Sancheong county were tested at baseline and two follow‐up surveys after 1 and 3 years. Faecal samples were examined for C. sinensis eggs using the Kato‐Katz method. Participants were divided into three intervention groups by areas and year recruited: national prevention programme only (mass health campaign and praziquantel treatment) for Group A; health education for community leaders added for Group B; and individual health education added for Group C. Results The prevalence of C. sinensis infection fell substantially in all three intervention groups between baseline and 3‐year follow‐up: from 31.1% to 14.9% in Group A, from 29.6% to 6.8% in Group B and from 21.9% to 8.6% in Group C. The control effectiveness was highest in Group B with 76.8%. The new infection rate was 16.3%, 12.8% and 7.6% in Group A, B and C, respectively. The reinfection rate was lower in Group B (3.8%) than Group C (12.2%). Conclusions To control C. sinensis infection in endemic areas of Korea, health education for community leaders or individuals on prevention of C. sinensis infection should be added to national control programmes.